Ion channels. - Conn, P. Michael (Methods in enzymology, 1998)
This volume plus its companion, Volume 294, presents cutting edge techniques for the study of ion channels, ranging from the molecular to the physiological level. These volumes supplement Volume 207 of Methods inEnzymology Key Features * Assembly * Genetics * Electrophysiology * Expression Systems * Model Simulations.